Advanced control strategies for PMSM drive system in high-performance electric racing application - Wang, Sunbo (2025)
This thesis presents advanced control strategies to improve the dynamic performance and efficiency of Silicon Carbide (SiC)-based Permanent Magnet Synchronous Motor (PMSM) drive systems, specifically for high-performance electric racing applications. It begins with the development of a comprehensive analytical loss model that captures the nonlinear behaviour of both the machine and power electronics. This model offers detailed insights into energy dissipation and serves as the foundation for optimising $dq$-axis current references. Experimental validation shows that predicted system losses align with measurements within a Normalized Root Mean Square Error (NRMSE) below 5%, confirming its suitability for efficiency optimisation.